PENGARUH METODE PLYOMETRIC TERHADAP KEMAMPUAN VERTICAL JUMP PADA SISWA EKSTRAKURIKULER BOLA VOLI DI SMKN 1 KAYONG UTARA - Pardik, Pardik; Supriatna, Eka; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractPardik (2021) The Effect of Plyometric Methods on Vertical Jump Women in Volleyball Extracurricular Students at SMKN 1 Kayong Utara (Supervisor I: Eka Supriatna M.Pd and Advisor II: Fitriana Puspa Hidasari M.Or). The problem in this study is the vertical jump ability of volleyball players at SMKN 1 Kayong Utara, who take volleyball extracurricular activities is still categorized as lacking and the plyometrix method has not been applied. The purpose of this study was "is there an effect of the plyometrix method on the vertcal jump ability of volleyball extracurricular students at SMKN 1 Kayong Utara. The purpose of this research is to increase the vertical jump ability. The population in this study were 20 students who took extracurricular activities at SMKN 1 Kayong Utara. Sampling in this study using a saturated sampling technique, namely the technique of determining the sample when all populations are used as samples. The form of research used in this research is Pre Experimental Design with the One-Group Pretest-Posttest Desingn model, which is a research design that is given a pretest before being given treatment, so the results of the treatment can be known to be more accurate. Based on the calculated chi square for pretest = 4.958 and posttest = 7.62 smaller than the chi squared table (9.488), the distribution of the 20 athletes' statistical data can be declared normal, F count is smaller than F table 2.28 4.38 for F table 5%, it can be concluded that the variant of the data to be analyzed is homogeneous. The calculation of the T test obtained the value of t count = 6.955 t table = 2.093. The percentage increase in vertical jump exercise using the plyometrix method is 19.5%. Thus, the vertical jump exercise using the plyometrix method is proven to have an effect on the jump height of students who take the Volleyball Extracurricular at SMKN 1 Kayong Utara.Keywords: plyometric, vertical jump